PARALLELISM OF THE PLOT BETWEEN NOVEL AND FILM LITTLE WOMEN - Nuri, Nur A B; Wanggai, Febe F I; Liru, Marianus W (Lantern: Journal of Language and Literature, 2023)
In this study, the writer analyzed the plot comparison in two literary works, namely the novel and the film Little Women. The purpose of this study is to found out the differences, similarities and parallels between the two literary works. The method used by the writer in this study is qualitative research. This study used the first theory from Drs. Meiliana Sylvie explained about comparative literature. Secondly, the writer used Shiquan Cao's theory that explained about the parallel. This study was conducted to found out the similarities, differences and parallel plots in the two literary works. The study focused on the plot in the story.The results of this study show that between the novel and the film Little Women have similarities and differences, namely exposition / equilibrum, rising action / distrubtion, climax / recognition, falling action / repair and resolution / equilibrum again, and also parallel, namely, parallel in differences, narrative and character. This study will identify important elements in the plot present in both works, and compare how the plot is presented and interpreted in the form of novels and films. This undergraduate thesis thus provides a more in-depth look at the way the two media convey the same story in different ways.